Políticas educacionais para a formação docente na educação básica - Maria Lília Imbiriba Sousa Colares (EccoS – Revista Científica)
The historical development of school education can be scaled through a series statistics and other quantitative data from the various factors that influenced the results are analyzed from the critical perspective. This involves the understanding that natural events are inter-related macro historical context. It was this perspective that permeated the research that resulted in this article and whose object of investigation were the educational policies of the Municipal Education from the municipality of Santarém-Pa, with regard to teacher training. The period (2003-2010) was due to the implementation of differentiated and innovative actions in the education sector since the adoption of the new LDB, 9.394/96. We emphasize that the educational policy expressed different degrees of understanding of the role of government in the face of effective social demands.